The effectiveness of telephone-delivered psychological therapies for depression and anxiety: A systematic review. (February 2018) - Coughtrey, Anna E; Pistrang, Nancy
Objectives: The telephone is increasingly used to deliver psychological therapies for common mental health problems. This review addressed the following question: are evidence-based psychological therapies for adults with depression and/or anxiety effective in reducing psychological symptoms when delivered over the telephone? Method: A systematic search for articles published over a 25-year period (January 1991–May 2016) was performed using the databases PsycINFO, PubMed and Web of Science. Citation searches, manual searches of bibliographies of relevant papers, and hand searches of key journals were also conducted. The quality of the studies included for review was assessed using the Effective Public Health Practice Project Quality Assessment Tool. Results: Fourteen studies met inclusion criteria for the review. Ten reported findings from telephone treatment for depression and four for anxiety. Nine studies used randomised controlled designs, two used quasi-experimental designs and three used uncontrolled designs. Thirteen studies reported reductions in symptoms of depression or anxiety. Cohen's d ranged from 0.25–1.98 (median = 0.61) for controlled studies and from 1.13–1.90 (median = 1.26) for uncontrolled studies. Only four studies reported clinically significant change. Conclusions: The findings indicate that telephone-delivered interventions show promise in reducing symptoms of depression and anxiety. Further research is required to establish the types of interventions that are most effective and the characteristics of clients who find them beneficial.